RUANG KESADARAN DIALEKTIK, MAMPANG PRAPATAN, JAKARTA SELATAN - Angelita Permatasari Angkola; Alvin Hadiwono (Jurusan Arsitektur dan Perencanaan, 2021)
Living in the middle of the hustle and bustle of urban modernization, a high city lifestyle, dense environmental conditions, and the demands of work make people feel psychological pressure, so that the risk of stress in urban areas increases. In addition, rapid technological advances make it easier for metropolitan citizen to get stressors (stressful situations). This makes it more difficult for individuals to deal with stress due to social, economic and environmental demands that continue to affect our surroundings. When the citizen often under prolonged stress, it can cause mild mental disorders such as depression and anxiety disorders. Urban stress is not only caused by a person's personal condition but can also be caused by cities that are not supported by facilities and infrastructure for psychological comfort in urban areas.Therefore, the project